KNOWLEDGE, ATTITUDE, AND PRACTICE TOWARD PHARMACOVIGILANCE AND ADVERSE DRUG REACTION REPORTING AMONG NURSING STAFF AND STUDENTS - B, Dharini; Reddy V, Nagarjuna; M, Deepalakshmi; A, Pramod Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study is to assess awareness of Pharmacovigilance among the healthcare professionals and to evaluate the impact of an educational intervention for improving awareness of Pharmacovigilance among the nursing staff and nursing students from Bengaluru, Karnataka, India. Methods: A cross-sectional study was carried out using a validated questionnaire that included demographic details and 20 survey items to evaluate the participants' knowledge, attitude, and perception (KAP) on adverse drug reactions (ADRs) and Pharmacovigilance. All participants received an interactive educational intervention in the form of a lecture. A pre- and post-KAP questionnaire survey was used to evaluate the impact of educational intervention among the participants. The Statistical Package for Social Sciences statistical software, version 16, was used to analyze the data. Results: A total of 103 healthcare professionals in the study responded to the pre- and post-KAP survey questionnaires. 66 nursing students and 37 nursing staff were involved in the study. The increased awareness among the study subjects about pharmacovigilance between pre- and post-intervention was statistically significant (p<0.001) which showed the effectiveness of educational intervention carried out. Conclusion: The results show that participants in the study were only moderately aware of ADR monitoring. However, they had expressed a positive attitude toward Pharmacovigilance and ADRs reporting. There is a need to create awareness among the nursing fraternity about ADR reporting for improving the spontaneous reporting.